Body Shaming and Self-Esteem: A Study Among First-Year Student - Azzahra, Putri Karini; Daulay, Wardiyah (Journal of Sumatera Sociological Indicators, 2025)
Body shaming is a form of verbal bullying carried out by one individual against another. It can be understood as inappropriate and harmful actions or expressions directed at physical appearance, whether towards oneself or others. If persistent, it can erode self-confidence and affect an individual's self-esteem. This study aims to determine the relationship between body shaming and self-esteem among first-year students of the Faculty of Nursing at Universitas Sumatera Utara. This research employs a quantitative associative correlation method with a cross-sectional approach, involving 215 first-year students selected through total sampling techniques. The research instrument used was a questionnaire. The results, analyzed using the Spearman rank test, indicated a p-value of 0.000 (<0.05), signifying a significant relationship between body shaming and self-esteem among first-year students of the Faculty of Nursing at Universitas Sumatera Utara. The findings revealed that body shaming was at a moderate level among 163 first-year students (75.8%), while self- esteem was also at a moderate level among 165 first-year students (76.7%). It is recommended that first-year students cultivate gratitude for their body shape, view themselves positively, and offer positive affirmations to themselves and others